Clinical and research priorities for children and young people with bronchiectasis: an international roadmap - KARADAĞ, BÜLENT TANER (EUROPEAN RESPIRATORY SOC JOURNALS LTD, 2021)
The global burden of children and young people (CYP) with bronchiectasis is being recognised increasingly. They experience a poor quality of life and recurrent respiratory exacerbations requiring additional treatment, including hospitalisation. However, there are no published data on patient-driven clinical needs and/or research priorities for paediatric bronchiectasis. Parent/patient-driven views are required to understand the clinical needs and research priorities to inform changes that benefit CYP with bronchiectasis and reduce their disease burden. The European Lung Foundation and the European Respiratory Society Task Force for paediatric bronchiectasis created an international roadmap of clinical and research priorities to guide, and as an extension of, the clinical practice guideline. This roadmap was based on two global web-based surveys. The first survey (10 languages) was completed by 225 respondents (parents of CYP with bronchiectasis and adults with bronchiectasis diagnosed in childhood) from 21 countries. The parent/patient survey encompassed both clinical and research priorities. The second survey, completed by 258 health practitioners from 54 countries, was limited to research priorities. The two highest clinical needs expressed by parents/patients were: having an action management plan for flare-ups/exacerbations and access to physiotherapists. The two highest health practitioners' research priorities related to eradication of airway pathogens and optimal airway clearance techniques. Based on both surveys, the top 10 research priorities were derived, and unanimous consensus statements were formulated from these priorities. This document addresses parents'/patients' clinical and research priorities from both the parents'/patients' and clinicians' perspectives and will help guide research and clinical efforts to improve the lives of people with bronchiectasis.
Keywords: CYSTIC FIBROSIS BRONCHIECTASIS; LUNG-FUNCTION; ERADICATION; DISEASE